2016
DOI: 10.1080/00016357.2016.1255352
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spheno-occipital synchondrosis, dental age, chronological age and cervical vertebrae maturation in Turkish population: is there a link?

Abstract: Good correlation was found between the degrees of TMM, fusion of SOS and CVM in young Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…In addition, the growth literature has shown a strong correlation between the peak height velocity and peak of facial growth [ 39 , 40 ]. In a recent study published by Demirturk Kocasarac et al [ 41 ], they found good correlation between cervical vertebra maturation that occurs during adolescence age and SOS fusion. All these together suggest SOS closure onset may precede the menarche and might occur at the same time as highest rate of facial growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the growth literature has shown a strong correlation between the peak height velocity and peak of facial growth [ 39 , 40 ]. In a recent study published by Demirturk Kocasarac et al [ 41 ], they found good correlation between cervical vertebra maturation that occurs during adolescence age and SOS fusion. All these together suggest SOS closure onset may precede the menarche and might occur at the same time as highest rate of facial growth.…”
Section: Discussionmentioning
confidence: 99%
“…The studies indicate that, in males, complete fusion of the spheno‐occipital synchondrosis can occur from 11 years (Demirturk Kocasarac et al, 2016; Kahana et al, 2003) and from 8 years in females (Powell & Brodie, 1963), with the possibility of fusion even by 6 years (Messineo & Mangiulli, 2018). They also indicate that, in males, incompletely closed synchondroses can still be seen at 26 years and over (Demirturk Kocasarac et al, 2017; Kahana et al, 2003) and in females to at least 24 years and over (Demirturk Kocasarac et al, 2016; Sinanoglu et al, 2016). Open synchondroses in the early twenties are well attested for both males (Akhlaghi et al, 2008, 2010; Coqueugniot & Weaver, 2007; Demirturk Kocasarac et al, 2016, 2017; Ekizoglu et al, 2016; El‐Barrany et al, 2015; Kahana et al, 2003; Shirley & Jantz, 2011; Sinanoglu et al, 2016) and females (Coqueugniot & Weaver, 2007; Demirturk Kocasarac et al, 2016, 2017; Ekizoglu et al, 2016; El‐Barrany et al, 2015; Sinanoglu et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…They also indicate that, in males, incompletely closed synchondroses can still be seen at 26 years and over (Demirturk Kocasarac et al, 2017; Kahana et al, 2003) and in females to at least 24 years and over (Demirturk Kocasarac et al, 2016; Sinanoglu et al, 2016). Open synchondroses in the early twenties are well attested for both males (Akhlaghi et al, 2008, 2010; Coqueugniot & Weaver, 2007; Demirturk Kocasarac et al, 2016, 2017; Ekizoglu et al, 2016; El‐Barrany et al, 2015; Kahana et al, 2003; Shirley & Jantz, 2011; Sinanoglu et al, 2016) and females (Coqueugniot & Weaver, 2007; Demirturk Kocasarac et al, 2016, 2017; Ekizoglu et al, 2016; El‐Barrany et al, 2015; Sinanoglu et al, 2016). The possible ranges of age of closure of the spheno‐occipital synchondrosis for males and females are thus both very large.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This important growth center is comprised of hyaline cartilage, which will be ossified during puberty, and is abundantly found at the base of the skull during growth. Knowing the chronological age of SOS ossification might result in various decisions in forensic, anthropological and medical practices (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%